LEARNING STYLES AND THEIR EFFECTIVENESS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Axmedjanova Farida Djavairovna; Ahmedov Sardor Habibullo o‘g‘li; Ashurova Nigora Axtamovna; Bekniyazova Dildoraxon Urazniyaz kizi; Akramova Sarvinoz Xoshimovna; Axmedova Nilufar Abdusattarovna (Western European Studies, 2025)
this article is designed to introduce a range of learning styles and how these may then be linked to the effectiveness of teaching EFL. It reviews the more familiar learning styles: visual, auditory, kinaesthetic, and reading/writing, and discusses each as it relates to how learners perceive and retain information. The study emphasizes how recognizing and accommodating variation in student learning style can facilitate motivation, participation, and language learning. The findings imply that a blended approach to teaching, where various methods are used, each appealing to different learning styles, will best facilitate effective teaching in the EFL context.
Keywords: learning styles; English as a foreign language; teaching effectiveness